Role of Forests in Carbon Sequestration - Bala, N.; Singh, G.; Kumar, Pramod; Sinha, A. K. (Indian Forester, 2003)
The size of the global forest carbon stock appears to be declining , thereby generating a net carbon source. While forest decline contributes to the build-up in atmospheric carbon , analysts widely agree that the primary cause of the build-up in atmospheric carbon is not attributable to land use changes , but rather is due largely to fossil fuel burning and its associated emissions. However , forestry can playa major role towards increasing the global carbon sequestration if the world's forest could be managed properly with due importance to afforestation and reforestation. Recognizing the role of forestry in carbon sequestration the 1997 Kyoto protocol specifically mentioned afforestation and reforestation as tools that can be used to reduce level of carbon dioxide from atmosphere.